2016
DOI: 10.2217/pme-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Case with Triple-Negative Breast Cancer Shows Overexpression of Both Cfos and Tgf-β1 in Node-Positive Tissue

Abstract: We present herein a case report style article on a rare advanced triple-negative breast cancer (TNBC) patient with 6-month disease-free interval, and 10-month overall survival. Our results demonstrate that the poor clinical outcome of this patient was associated with pronounced, more than fivefold higher, overexpression of both cFOS and TGF-β1 proteins in its metastatic nodal tissue extracts, when compared with the values of the two non-TNBC controls (with 'zero' disease-free interval and overall survival). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Considerable research attention has been focussed on a role of deregulation of Transforming Growth Factor β1 (TGFβ1) as tumor promoter step favoring BC invasion and metastasis [ 7 ]. Moreover, accumulating evidence shows that FOS transcription factor binding motifs are critical for the regulation of TGFβ1 expression [ 8 ]. Thus, cFOS elevation may have utility as a complementary candidate biomarker of BC invasiveness, co-expressed with TGFβ1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable research attention has been focussed on a role of deregulation of Transforming Growth Factor β1 (TGFβ1) as tumor promoter step favoring BC invasion and metastasis [ 7 ]. Moreover, accumulating evidence shows that FOS transcription factor binding motifs are critical for the regulation of TGFβ1 expression [ 8 ]. Thus, cFOS elevation may have utility as a complementary candidate biomarker of BC invasiveness, co-expressed with TGFβ1.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cFOS elevation may have utility as a complementary candidate biomarker of BC invasiveness, co-expressed with TGFβ1. Consequently, we have previously proposed that cFOS and TGFβ1 proteins may be considered as a pair of biomarkers of an early assessment of invasive BC [ 7 , 8 ], providing adequate invasive BC specimens are available. In the past, primary tumor tissue had been fractionated into nuclear [ 9 ] or cytosolic [ 10 , 11 ] extract to assess specific biomarkers of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we reported that pS134-GR species are elevated in TNBC relative to luminal breast cancer subtypes [16]. Since TGFβ1 expression is also elevated in TNBC and associated with poor outcome, we predicted tight linkage between TGFβ1 signaling and phosphorylation of GR Ser134 [42,43]. MDA-MB-231 cells were treated with 10 ng/mL TGFβ1 for 30 min, 1 h, and 2 h; phosphorylation of GR Ser134 was induced by TGFβ1 at 1 h and 2 h. Additionally, p38 MAPK activity, as measured by active-site phosphorylation, was also elevated at these timepoints (Fig.…”
Section: Tgfβ1 Induces Tnbc Cell Migration Via Phosphorylation Of Gr Ser134mentioning
confidence: 83%
“…Consequently, we have, previously proposed that cFOS and TGFβ1 proteins may be considered as a pair of biomarkers of an early assessment of invasive BC (7,8), providing adequate invasive BC specimens are available. In the past, primary tumor tissue had been fractionated into nuclear (9) or cytosolic (10,11) extract to assess speci c biomarkers of interest. Until recently, however, the protocol for fractionation of mALN nuclear and cytosolic extracts has not been available, presumably due to the speci c tough, brous nature of mALN tissue.…”
Section: Considerable Research Attention Has Been Focused On a Role Of Deregulation Of Transforming Growthmentioning
confidence: 99%